Seminar Edukasi Pelajar sebagai Agen Perubahan untuk Pengembangan Sumber Daya Manusia Menuju Indonesia Emas 2045 - Hardika Saputra (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
This community service activity aims to enhance students' awareness and role as agents of change in the development of human resources towards the Golden Indonesia 2045. The seminar held at SMA Muhammadiyah Ahmad Dahlan Metro on January 6, 2025, involved 150 students. The method used was an educational approach involving leadership training, group discussions, and providing materials about the importance of students' contribution to social change. The results of this activity showed an increase in students' understanding of social responsibility and leadership, as well as the emergence of local leaders among students who are ready to actively contribute to society. Additionally, this activity successfully changed students' behavior in increasing social participation and their awareness of the importance of sustainable development. This seminar is expected to serve as a model for wider community service activities in the future, involving more student communities in realizing the Golden Indonesia 2045.